2014
DOI: 10.1016/j.chom.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hepatitis C Virus Entry on Viral Tropism

Abstract: Uptake of hepatitis C virus (HCV) into hepatocytes is an orchestrated process, involving numerous host factors, virion-associated lipoproteins and a growing number of cell-associated factors. Several of these factors likely contribute to the hepatotropism and limited host range of this virus. Discerning the minimal set of human-specific factors required for viral uptake into non-human cells has facilitated the development of small animal models with inheritable HCV susceptibility. This review summarizes curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 43 publications
0
60
0
2
Order By: Relevance
“…We should point out that this mouse model is not without caveats. For example, since not all of the identified human receptors/cofactors for HCV (17) are present in the model, it may be easier to prevent infection in the model than with natural infection. Nevertheless, we have previously shown that levels of protection correlate well with the immunogenicity of vectored vaccines in the model (12), and thus, such humanized mice seem adequate for evaluating the efficacy of our recombinant HCV vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should point out that this mouse model is not without caveats. For example, since not all of the identified human receptors/cofactors for HCV (17) are present in the model, it may be easier to prevent infection in the model than with natural infection. Nevertheless, we have previously shown that levels of protection correlate well with the immunogenicity of vectored vaccines in the model (12), and thus, such humanized mice seem adequate for evaluating the efficacy of our recombinant HCV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the extreme genetic and antigenic diversity across and within HCV genotypes, this has been a particularly challenging goal (15). The HCV envelope proteins E1 and E2 are responsible for mediating HCV entry into target cells by direct or indirect interaction with numerous host molecules (16,17) and are thus the natural targets of NAbs (18). Consequently, all experimental HCV vaccines that aim to generate NAbs contain E2 and/or E1 components in a variety of modalities or prime-boost regimens (19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Nevertheless, experiments with CSFV and antibodies against the porcine CD46 suggest that porcine CD46 plays a role for CSFV entry, but the inhibitory effect remained rather weak, suggesting involvement of additional factors (Dräger, Beer, & Blome, 2015). The related HCV was shown to use at least four different entry factors (for a review, see Ding, von Schaewen, & Ploss, 2014;. For pestiviruses, evidence so far suggests that a first attachment might be due to the interaction of E rns with glycosaminoglycans (Hulst et al, 2000Iqbal et al, 2000).…”
Section: E2mentioning
confidence: 99%
“…Among the many host factors, human-specific CD81 and OCLN are sufficient for entry and replication of HCV in murine cells in vitro and in vivo, suggesting that the host tropism of HCV is mostly defined by entry receptors [81]. Interestingly, mouse hepatic cell lines endogenously expressing miR-122 and ApoE support the replication of viral RNA and formation of infectious HCV particles, indicating that apolipoproteins are not involved in the host tropism of HCV [82,83].…”
Section: Apolipoproteins Are Key Determinants For Hepatic Tropism Of Hcvmentioning
confidence: 99%